Systematic location of the ‘absence of harmful conduct’ in the theory of crime (2021)
This reflection article aims to show the several proposed solutions at doctrinal level to the legal problems arising from the question pertaining to the systematic location of the "absence of harmful conduct" in various of the dogmatic and structural theory of crime categories, and then show which is the jurisprudential line that the Criminal Cassation Chamber of the Supreme Court has handled in this regard, proposing then a solution from the framework of Objective Imputation that can be fully satisfactory and coherent with the gears of the Constitutional Laws that govern the Criminal Law and Penal Procedures of Colombia. To fulfill this objective, the construction of jurisprudential lines and the dogmatic method were used as research methods.